1975
DOI: 10.1136/adc.50.3.235
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic acid and tyrosine metabolism in preterm and small-for-dates infants.

Abstract: Hyderabad, IndiaMohanram, M., and Kumar, A. (1975). Archives of Disease in Childhood, 50, 235. Ascorbic acid and tyrosine metabolism in preterm and small-fordates infants. Ascorbic acid levels in plasma and leucocytes and urinary excretion of tyrosyl derivatives (TD) were determined in 11 normal, 18 preterm, and 4 smallfor-dates infants.Concentrations of ascorbic acid in both plasma and leucocytes were found to be similar in the 3 groups. There was no difference in the basal levels of TD between normal and sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1978
1978
1986
1986

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Early studies suggested that supplementation with ascorbate or folate, or both, would alleviate these biochemical abnormalities. Systematically controlled studies performed more recently (Bakker et al, 1975;Partington and Mathews, 1967;Mohanram and Kumar, 1975), however, indicate that the tyrosinemia and tyrosyluria found in preterm infants fed high-protein diets is not corrected by massive doses of either vitamin. Plasma concentrations of phenylalanine as high as those found in phenylketonuria were observed in a few preterm infants fed a formula providing 4.5 protein/kg-day of a caseinpredominant formula .…”
Section: Oxidation Of Phenolic Amino Acidsmentioning
confidence: 99%
“…Early studies suggested that supplementation with ascorbate or folate, or both, would alleviate these biochemical abnormalities. Systematically controlled studies performed more recently (Bakker et al, 1975;Partington and Mathews, 1967;Mohanram and Kumar, 1975), however, indicate that the tyrosinemia and tyrosyluria found in preterm infants fed high-protein diets is not corrected by massive doses of either vitamin. Plasma concentrations of phenylalanine as high as those found in phenylketonuria were observed in a few preterm infants fed a formula providing 4.5 protein/kg-day of a caseinpredominant formula .…”
Section: Oxidation Of Phenolic Amino Acidsmentioning
confidence: 99%